2005
DOI: 10.1113/jphysiol.2005.094805
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term in vivo modulation of synaptic efficacy at the neuromuscular junction of Rana pipiens frogs

Abstract: Prolonged changes in motor neurone activity can result in long-term changes in synaptic transmission. We investigated whether mechanisms commonly thought to be involved in determining synaptic efficacy of vertebrate motor neurones are involved in these long-term changes. The nerve supplying the cutaneus pectoris muscle was chronically stimulated via skin surface electrodes in freely moving frogs for 5-7 days. Chronic stimulation induced a 50% reduction in evoked endplate potential (EPP) amplitude at stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…A similar presynaptic effect has been reported recently in vivo with chronic stimulation at the neuromuscular junction (Belair et al, 2005), indicating that these mechanisms are likely to be important in many forms of synaptic plasticity. It will be of great interest to determine under what conditions synaptic vesicle priming assumes the primary role in homeostatic modulation and to determine the molecular pathways involved in the induction and expression of this form of synaptic plasticity.…”
Section: Comparison With Previous Resultssupporting
confidence: 82%
“…A similar presynaptic effect has been reported recently in vivo with chronic stimulation at the neuromuscular junction (Belair et al, 2005), indicating that these mechanisms are likely to be important in many forms of synaptic plasticity. It will be of great interest to determine under what conditions synaptic vesicle priming assumes the primary role in homeostatic modulation and to determine the molecular pathways involved in the induction and expression of this form of synaptic plasticity.…”
Section: Comparison With Previous Resultssupporting
confidence: 82%
“…Inhibition of protein kinase C blocked potentiation and mitochondrial calcium release. Chronic stimulation of frog motor neurons resulted in a large decrease in synaptic depression which was associated with increased mitochondrial energy metabolism and a larger presynaptic calcium signal, suggesting roles for mitochondria in synaptic calcium handling and efficacy [29]. Recordings from crayfish neuromuscular junctions showed that posttetanic potentiation (PTP), a process mediated by presynaptic Ca 2+ influx, is blocked when mitochondrial Ca 2+ uptake is inhibited [30] suggesting that PTP results from the slow release of Ca 2+ from mitochondria.…”
Section: Roles For Mitochondria In Synaptic Plasticitymentioning
confidence: 99%
“…Electron microscopy shows heterogeneous Ca 2+ sequestration within ER and mitochondria in the dendrites of hippocampal neurons (Pivovarova et al, 2002) and pharmacological exclusion of ER or mitochondria from Ca 2+ buffering modifies synaptic potentials (Markram et al, 1995;Billups and Forsythe, 2002;Medler and Gleason, 2002;Belair et al, 2005). It remains unclear, however, whether and how the neuronal activity is dependent on the spatiotemporal distribution of ER and mitochondria and which role the interactions between the organelles might play.…”
Section: Introductionmentioning
confidence: 99%
“…ER and mitochondria are involved in the modulation of synaptic transmission (Markram et al, 1995;Billups and Forsythe, 2002;Medler and Gleason, 2002;Belair et al, 2005). The disturbances in [Ca 2+ ] i handling by these organelles can cause necrosis and apoptosis (White et al, 2005).…”
Section: Journal Of Cell Science 119 (23)mentioning
confidence: 99%